Prognostic value of lymph node micrometastasis in esophageal cancer: A systematic review and meta-analysis - Yang, Jing; Liu, Qianqian; Bai, Yuping; Zhao, Haitong; He, Tingting; Zhao, Ziru; Huang, Min; Jiang, Mengyuan; Zhang, Rui; Zhang, Min (Frontiers in Oncology, 2023)
Objective: Whether lymph node micrometastasis (LNM) increases the risk in esophageal cancer patients remains controversial. We conducted a systematic review and meta-analysis to explore the prognosis value of LNM in esophageal cancer patients. Methods: Two reviewers independently searched electronic databases, including PubMed, Embase, and the Cochrane Library, for eligible citations until February 2022. We calculated pooled estimates of the hazards ratio with a random-effects model. The certainty of evidence was determined by the Grade of Recommendations Assessment, Development, and Evaluation (GRADE) method. A sensitivity analysis was performed to assess the stability. Publication bias was assessed using funnel plots and Egger's test. We also performed subgroup analysis to explore the source of heterogeneity. Results: A total of 16 studies, with 1,652 patients, were included. The overall survival (OS) was significantly increased with LNM negativity compared with LNM positivity (HR 1.95; 95% CI, 1.53–2.49; P < 0.001; I2 = 0.0%, P = 0.930; certainty of evidence: low). Relapse-free survival (RFS) was significantly increased with LNM negativity compared with LNM positivity (HR 3.39; 95% CI, 1.87–6.16; P < 0.001; I2 = 50.18%, P = 0.060; certainty of evidence: moderate). No significant difference was observed in recurrence between the two groups (certainty of evidence: low). Sensitivity analysis revealed a stable trend. In addition, the funnel plot and Egger's test did not show significant publication bias. Conclusion: LNM positivity worsens the prognosis in esophageal cancer, and the evidence for RFS is moderate. Future relevant high-quality studies are warranted to validate our results further and provide a reference for guidelines.